Enhancing Primary School Students' Motor Skills through Interactive Digital Learning Media: A Quasi-Experimental Study in Physical Education - Indra Adi Budiman (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of digital technology in education has opened new opportunities to enhance student engagement and learning outcomes. In physical education, interactive digital learning media offers potential to improve motor skills among primary school students, a critical developmental aspect often overlooked in technology-based learning. This quasi-experimental study investigated the effect of interactive digital learning media on the motor skills of fourth- and fifth-grade students in a public elementary school in Majalengka Regency, Indonesia. A total of 60 students were purposively selected and divided equally into experimental (n=30) and control (n=30) groups. The experimental group used interactive digital media, while the control group received conventional instruction. Motor skills were measured through agility, coordination, and balance tests. Additional data were collected via questionnaires and teacher-student interviews. Independent t-tests were used for statistical analysis, and thematic analysis was applied to qualitative data. The experimental group showed significantly higher improvement in all motor skill areas (p 0.05) compared to the control group. Thematic findings revealed that students experienced greater motivation, enjoyment, and understanding through digital simulations and feedback. Teachers also reported improved engagement and ease in delivering motor skill instruction. The findings confirm that interactive digital media can effectively enhance motor skills and learning motivation in primary physical education, aligning with multimedia learning theory. These results support integrating technology into physical education to promote cognitive, affective, and psychomotor development.